EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN METODE DARING DI SMAN KOTA PARIAMAN - nurul hamini; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
Abstrak This study aims to find out about (1) the effectiveness of online learning (2) to find out what problems are faced in online learning (3) to find out what solutions can be done in order to overcome online problems in Kota Pariaman. This type of research uses descriptive quantitative research, data collection techniques use observation techniques, interviews, questionnaires and documentation techniques. Then the informants in this study were geography teachers of SMAN Kota Pariaman and also students of SMAN Kota Pariaman. Furthermore, for data analysis techniques used descriptive data analysis techniques and descriptive statistical calculations using percentage descriptive statistics. The results of this study are (1) The effectiveness of online learning at SMAN Kota Pariaman is: Learning using online methods at SMAN Kota Pariaman is still not effective. Because the management of learning during the Covid pandemic was shifted to online learning, teacher and student communication did not go so well, so that students responded and responded to learning using online methods. Student learning activities do not run properly because there is a lack of response and feedback between teachers and students so that student learning outcomes decline. This is what causes the online learning process to be less effective, including in the